The Influence Of Educational Resources, Geographic Conditions, Demographic Conditions, Economic Conditions, Population Capacity on Junior High School Gross Participation Rate - Nurulpaik, Iik; Permana, Johar; M. Mirfani, Aceng; Suryana, Asep (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2021)
The success of education development will be largely determined by the availability of educational resources as the main variable in providing educational services. Other factors are geographical conditions, demographic conditions, economic conditions, and the capacity of the population itself. This study examines the correlational-contributive relationship between these factors with the Gross Participation Rate (GER) in junior high schools in West Java. The data studied were 2015-2019 (5 years). Quantitative research methods with descriptive analysis. The results showed that the educational resources variable can explain the effect of 88, 14% on the total GER. The geographical condition variable can explain the effect of 63.96% on the total GER. The demographic condition variable explains the effect of 94.2% on the total GER and the KE variable contributes approximately 89.21% to the achievement of the total GER for SMP. The population capacity variable gave a valuable contribution of 37.96%.